Difficulties in diagnosing lymphatic malformations. - Garofalo, L. (European Journal of Pediatric Dermatology, 2020)
The late appearance of the neoformation, the initial warty appearance, the recurrence after removal, its progressive increase, the interpretative problems of the biopsy, the superficial ulceration and the hard consistency on palpation justify the uncertainties in the clinical diagnosis and the suspicion, which later proved unfounded, of a malignant neoformation. With hindsight, after having seen the histological examination of the excised neoformation, we understood the initial warty appearance – it is known that lymphangioma circumscriptum can present a warty appearance (1, 2) –, the nature of the small, sometimes translucent papules on the plaque and peripheral skin, corresponding to the frog-eggs, which are typical of lymphangioma circumscriptum, and the superficial ulceration due to the rupture of the epidermis stretched by superficial lymphatic cavities.